(untitled) (Biological Sciences - PJSIR, 1995)
Lead content of Leafy vegetables and tomatoes were determined for over a period of four months i.e. March - June, 1993 at Erekesan Market in Ado-Ekiti. The samples were taken at four different locations. The result shows a hi.gherlead content for the samples taken along the major roads when compared with the samples taken few meters away from the major roads. Lead concentration in tomatoes was generally higher than in vegetables at each location.